HUMAN DEVELOPMENT INDEX, UNEMPLOYMENT AND POVERTY IN PAPUA PROVINCE, 2010-2015 - Nurisqi Amalia; Anisa Nurpita; Rina Oktavia (Jurnal Ekonomi Pembangunan, 2018)
Papua Province is one of the poorest provinces in Indonesia. Some of the variables that affect health levels including Human Development Index (HDI) and unemployment rate. This research analyzes Human Development Index and unemployment rate to poverty level in districts/cities in Papua Province during 2010-2015. Research data used in this research is secondary data from Central Bureau of Statistics of district/city in Papua Province. The independent variables used are open unemployment rate and Development Index. While the dependent variable used is poverty level in districts/citis in Papua Province year 2010-2015. The analysis tool used is regression with panel data. The result of this research shows that the average of district/city’s poverty rate in Papua 2010-2015 is 32,34 percent. The highest level is in District Deiyai and the lowest is in District Merauke. The Human Development Index has decreased significantly to the poverty rate of district/city in Papua Province, while the open unemployment rate is positive to the poverty rate of district/city in Papua Province. Human Development Index and open unemployment rate as a whole and together affect poverty level in district/city in Papua Province.